Phonological acquisition among Malaysian English Child Speakers Of Indian descent - Thomas Joseph, Pamela (penerbit ukm, 2006)
This preliminary study aims to provide an initial description of phonological acquisition among Malaysian Children of Indian descent aged two to six years. The description of the consonantal phonemic inventory as well as various Phonological processes evidenced by subjects is also reported. The mothers’ phonemic inventory was obtained as the representation of the children’s most active environmental linguistic input. Speech samples of the mothers as well as the subjects were obtained from a single word test and narrative test. The speech sample was recorded and transcribed using the International Phonetic Alphabet. The results of the tests revealed a significant correspondence between the subjects’ phonemic inventory and their mothers’ except for the following phonemes: /ð/ , / θ / , /v/ and /w/. Both mothers and subjects demonstrated free variation for the production of /v/ and /w/. The mothers displayed a range of 21-23 phonemes in their inventories whereas the subjects displayed a range of 17-21 phonemes. The age acquisition for some phonemes, namely the affricates which was evidenced by subject aged 2;4 were noted to be earlier than that of subjects in past studies. Rapid phonological development was evidenced at the age of 2;4- 3;7.